PSYCHOLOGICAL ASPECTS OF THE FORMATION OF MORAL CONSCIOUSNESS IN STUDENTS - Akramov Mirmuxsin Rustamovich (American Journals Publishing, 2024)
In the article there is considered the issue of moral ideas of students during their study in higher education institution
Keywords: Behaviour, moral consciousness, moral problems, moral scales, discriminant, analyses.